Solution of Nonlinear Fredholm Integral Equations on Almost Z⊥-Contraction - Gunasekaran Nallaselli; Arul Joseph Gnanaprakasam; Gunaseelan Mani; Khalil Javed; Yahya Almalki (Journal of Mathematics)
In this manuscript, we develop an orthogonal to basically Z-contraction and demonstrate various fixed point theorems of nonlinear Fredholm integral equation solutions in such a contraction. By using these ideas of discovering the fixed point theorems, we can also build the application of the Fredholm integral equation.